A collaborative EDNAP exercise on SNaPshot™-based mtDNA control region typing. (January 2017) - Weiler, N.E.C.; Baca, K.; Ballard, D.; Balsa, F.; Bogus, M.; Børsting, C.; Brisighelli, F.; Červenáková, J.; Chaitanya, L.; Coble, M.; Decroyer, V.; Desmyter, S.; et al.
Abstract: A collaborative European DNA Profiling (EDNAP) Group exercise was undertaken to assess the performance of an earlier described SNaPshot™-based screening assay (denoted mini-mtSNaPshot) (Weiler et al., 2016) [1] that targets 18 single nucleotide polymorphism (SNP) positions in the mitochondrial (mt) DNA control region and allows for discrimination of major European mtDNA haplogroups. Besides the organising laboratory, 14 forensic genetics laboratories were involved in the analysis of 13 samples, which were centrally prepared and thoroughly tested prior to shipment. The samples had a variable complexity and comprised straightforward single-source samples, samples with dropout or altered peak sizing, a point heteroplasmy and two-component mixtures resulting in one to five bi-allelic calls. The overall success rate in obtaining useful results was high (97.6%) given that some of the participating laboratories had no previous experience with the typing technology and/or mtDNA analysis. The majority of the participants proceeded to haplotype inference to assess the feasibility of assigning a haplogroup and checking phylogenetic consistency when only 18 SNPs are typed. To mimic casework procedures, the participants compared the SNP typing data of all 13 samples to a set of eight mtDNA reference profiles that were described according to standard nomenclature (Parson et al., 2014) [2], and indicated whether these references matched each sample or not. Incorrect scorings were obtained for 2% of the comparisons and derived from a subset of the participants, indicating a need for training and guidelines regarding mini-mtSNaPshot data interpretation.